A jurisprudência como fundamento de validade das decisões judiciais - Castro, Sergio Monteiro Cupertino de (2012)
This dissertation is to analyze the normative meaning of Article 557 of the Code of Civil Procedure. That legislative statement introduced in the subsystem of civil procedural law legal rule of jurisdiction for the trial of civil appeals on the grounds of validity in the dominant jurisprudence of the courts. Therefore, the case will be considered as the basis of validity of judgments. Was taken as a starting point the correlation between culture, language and the right to fix the positive law as a linguistic system. Then we started to analyze the normative species, in particular the standards of competence, to establish the system of positive law as a self-referential system. The conditions were examined before expiration of the legal standards under the reference system of the theory of speech acts and normative discourse analysis. With these assumptions, we evaluated the powers of the State, in particular the jurisdiction. With these assumptions inferred from the norm of judgment prescribed in the wording of Article 557 of the Code of Civil Procedure. At the end, we started to look at some practical issues related to the therm.